Muscle-tendon interaction and elastic energy usage in human walking - Ishikawa, Masaki; Komi, Paavo V; Grey, Michael J; Lepola, Vesa; Bruggemann, Gert-Peter (Journal of applied physiology (1985), 2005)
The present study was designed to explore how the interaction between the fascicles and tendinous tissues is involved in storage and utilization of elastic energy during human walking. Eight male subjects walked with a natural cadence (1.4 +/- 0.1 m/s) on a 10-m-long force plate system. In vivo techniques were employed to record the Achilles tendon force and to scan real-time fascicle lengths for two muscles (medial gastrocnemius and soleus). The results showed that tendinous tissues of both medial gastrocnemius and soleus muscles lengthened slowly throughout the single-stance phase and then recoiled rapidly close to the end of the ground contact. However, the fascicle length changes demonstrated different patterns and amplitudes between two muscles. The medial gastrocnemius fascicles were stretched during the early single-stance phase and then remained isometrically during the late-stance phase. In contrast, the soleus fascicles were lengthened until the end of the single-stance phase. These findings suggest that the elastic recoil takes place not as a spring-like bouncing but as a catapult action in natural human walking. The interaction between the muscle fascicles and tendinous tissues plays an important role in the process of release of elastic energy, although the leg muscles, which are commonly accepted as synergists, do not have similar mechanical behavior of fascicles in this catapult action.